Determination of Stubble Yields and Quality in Wheat and Barley Growing Areas in Çanakkale - Hatice Simay Sarı; Fırat Alatürk (Acta Natura et Scientia)
This study was carried out to determine the yield, composition and forage quality of wheat and barley stubbles collected from the harvested fields of the said crops. The experiment was conducted in Çanakkale during the crop growing seasons of 2021 and 2022. In this study, the yields, compositions (ratios of stalk, leaf, weed and spike), along with the quality of forage (crude protein, crude ash, NDF, ADF, ADL, TSBM, ME, SE and the energy values of NE) of fresh and dry stubbles, taken from wheat and barley fields, were investigated. An average of 297.5 kg/da stubble yields were obtained as the result of this study. Consequently, it has been revealed that the average dry stubble yields of barley fields were 5.7% higher than that of the wheat stubbles. Hence, the average stubble dry matter ratio was recorded as 86.8%. It is concluded that the 44.7%, 44.2%, 5.8% and 5.3% of the stubbles of both plant species formed the stalk, leaf, spike and weed, respectively. The average crude protein, crude ash, NDF, ADF and ADL ratios of the stubbles were noted as 9.9%, 10.9%, 65.5%, 45.7% and 7.7%, respectively. The energy values of barley stubble were found to be higher, while the total digestible nutrient matters were recorded as an average of 55.6%. The overall results of this study showed that the nutrient content of stubble obtained from barley fields has better properties in terms of animal nutrition as compared to the stubbles of wheat.